Liquid compositions comprising particles of conductive polymer and organic solvent forming azeotrope with water
By adding high-boiling organic solvents to the PEDOT/PSS dispersion to form an azeotrope with water, and adding an appropriate amount of low-boiling solvents and other additives, the problem of excessive drying of the PEDOT/PSS dispersion is solved, and the stable operation of the equipment and the high-performance application of the conductive layer is achieved.
Patent Information
- Application Number
- JP2024190929
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-06-28
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2039-06-26
AI Technical Summary
The existing PEDOT/PSS dispersions dry too quickly when contacting air, causing equipment to be blocked, affecting the normal operation of the application equipment, and the addition of high boiling point solvents will lead to an increase in the resistance of the conductive layer, affecting its performance in some electronic devices.
Using a liquid composition containing polythiophene and polyanionic composite, a high boiling point organic solvent is used to form an azeotrope with water, adjusting the solubility and drying rate of the solution, while adding an appropriate amount of low boiling point solvent and other additives to maintain the performance of the conductive layer.
Effectively prevents equipment clogging while maintaining the high resistance and transparency of the conductive layer. It is suitable for a variety of electronic devices, especially OLED and OPV devices.
Smart Images

Figure 2025020254000001 
Figure 2025020254000002 
Figure 2025020254000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a liquid composition comprising particles comprising a complex of a polythiophene and a polyanion, a method for producing a layered body, a layered body obtainable by such a method, and uses of the liquid composition. [Background technology]
[0002] Conductive polymers are gaining increasing economic importance because polymers have advantages over metals in terms of processability, weight, and targeted tuning of properties by chemical modification. Examples of known π-conjugated polymers are polypyrrole, polythiophene, polyaniline, polyacetylene, polyphenylene, and poly(p-phenylene-vinylene). Layers of conductive polymers are employed in various industrial applications as polymer counterelectrodes in capacitors or for through-plating of electronic circuit boards. The preparation of conductive polymers is carried out chemically or electrochemically by oxidation from monomer precursors, such as optionally substituted thiophenes, pyrroles, and anilines, as well as certain optionally oligomeric derivatives thereof. In particular, chemical oxidative polymerization is widely used due to its ease of industrial realization in liquid media or on a variety of substrates.
[0003] A particularly important polythiophene used industrially is poly(3,4-ethylenedioxy-thiophene) (PEDOT or PEDT), which is described, for example, in US Pat. No. 5,399,633 and is prepared by chemical polymerization of 3,4-ethylenedioxythiophene (EDOT or EDT) and has a very high electrical conductivity in its oxidized form. An overview of the large number of poly(3,4-alkylenedioxythiophene) derivatives, in particular poly(3,4-ethylenedioxythiophene) derivatives, as well as their monomer units, synthesis and use, is given by J. P. Klein, “Polymerization of Poly(3,4-alkylenedioxythiophene) and Poly(3,4-ethylenedioxythiophene) Derivatives,” 1999, 143:1311-1325 (2003). Often, 3,4-ethylenedioxythiophene is polymerized in water in the presence of a polyanion, such as polystyrene sulfonate (PSS), thereby obtaining an aqueous composition comprising a complex of cationic polythiophene and polyanion (often called “PEDOT / PSS”). Such a process is disclosed, for example, in US Pat. No. 5,399,633. Due to the polyelectrolyte properties of PEDOT as polycation and PSS as polyanion, these compositions are not true solutions but rather dispersions. In this context, the degree to which the polymer or polymer moieties are dissolved or dispersed depends on the weight ratio of polycation and polyanion, the charge density of the polymer, the salt concentration of the environment, and the nature of the surrounding medium (Non-Patent Document 2).
[0004] PEDOT / PSS dispersions have gained particular industrial importance. They have found numerous uses as antistatic coatings or conductive layers in electronic components, for example as hole injection layers in organic light-emitting diodes (OLEDs), intermediate layers in organic photovoltaic devices (OPV devices) or organic photodetectors (OPDs) or as electromagnetic interference (EMI) shielding materials, transparent conductive films. They are also commonly used for the formation of conductive polymer layers, in particular solid electrolyte layers or polymer outer layers, in the manufacture of solid electrolyte capacitors.
[0005] However, aqueous PEDOT / PSS dispersions known from the prior art often dry too quickly on contact with air, which leads to clogging of the equipment used to apply these dispersions onto substrates, such as slot-die coaters, inkjet printers or spray nozzles. To slow down the drying rate of aqueous PEDOT / PSS dispersions, high-boiling point solvents such as ethylene glycol and DMSO (i.e. solvents with a boiling point higher than that of water) have been added. Such an approach is disclosed, for example, in US Pat. No. 5,399,363. However, the addition of such high-boiling point solvents also leads to a significant decrease in the sheet resistance of the resulting conductive polymer film, which is undesirable when the conductive polymer layer is used as an antistatic coating, as an electromagnetic radiation shield, or as a hole transport layer in organic light-emitting diodes (OLEDs) or organic photovoltaic (OPV) devices or organic photodetectors (OPDs). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] European Patent No. 0 339 340 A2 [Patent Document 2] European Patent No. 0 440 957 A2 [Patent Document 3] European Patent No. 0 686 662 A2 [Non-patent literature]
[0007] [Non-Patent Document 1] A. Elschner, S. Kirchmeyer, W. Loevenich, U. Merker, K. Reuter “PEDOT Principles and Applications of an Intrinsically Conductive Polymer”, CRC Press 2011 [Non-Patent Document 2] V. Kabanov,Russian Chemical Reviews 74,2005,3-20 Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention was based on the object of overcoming the drawbacks arising from the prior art in relation to liquid compositions comprising polythiophenes, in particular PEDOT / PSS dispersions. [Means for solving the problem]
[0009] In particular, the present invention is based on the object of providing liquid compositions comprising polythiophenes that can be used for the formation of conductive layers having a sufficiently high sheet resistance that allows the use of the compositions for the formation of antistatic coatings or electromagnetic radiation shields or for the preparation of hole transport layers in organic light emitting diodes (OLEDs) or organic photovoltaic (OPV) devices or organic photodetectors (OPDs), which do not lead to clogging of the equipment used to apply these dispersions on substrates, such as inkjet printers or spray nozzles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] |1| A liquid composition comprising: i) particles comprising a complex of a polythiophene and a polyanion; ii) a liquid phase, said liquid phase comprising: iia) Water and iib) or less a boiling point in the range of 110 to 250°C, preferably in the range of 120 to 225°C and most preferably in the range of 130 to 200°C, measured at a pressure of 1013 mbar, and - a solubility in water of at least 10% by weight, preferably at least 25% by weight, more preferably at least 50% by weight, and most preferably at least 90% by weight, measured at 25°C; At least one organic solvent having and includes; Including, The liquid phase is or can form an azeotrope; liquid composition.
[0011] |2| A liquid composition according to embodiment |1|, wherein the liquid composition is a dispersion in which particles i) are dispersed in a liquid phase ii).
[0012] |3| The liquid composition according to embodiment |1| or |2|, wherein the polythiophene is poly(3,4-ethylenedioxythiophene) (PEDOT).
[0013] |4| The liquid composition according to any one of embodiments |1| to |3|, wherein the polyanion is an anion of polystyrene sulfonic acid (PSS).
[0014] |5| The liquid composition according to any one of embodiments |1| to |4|, wherein the complex of polythiophene and polyanion is a PEDOT / PSS complex.
[0015] |6| Weight average diameter (d 50 ) is in the range of 10 nm to 2000 nm, more preferably in the range of 20 nm to 500 nm, and more preferably in the range of 25 nm to 50 nm.
[0016] |7|A liquid composition according to any one of embodiments |1| to |6|, wherein the organic solvent iib) is an alcohol, preferably ethyl glycol, butyl glycol or diacetone alcohol, an ether, preferably diethylene glycol dimethyl ether (Diglyme), or a mixture thereof.
[0017] |8|The liquid composition according to embodiment |7|, wherein the organic solvent iib) is an alcohol.
[0018] |9| The liquid composition according to embodiment |8|, wherein the alcohol is selected from the group consisting of ethyl glycol, butyl glycol, diacetone alcohol or a mixture thereof.
[0019] |10|The liquid composition according to embodiment |9|, wherein the alcohol is diacetone alcohol.
[0020] |11|The liquid composition described in embodiment |9|, wherein the alcohol is ethyl glycol.
[0021] |12|The liquid composition described in embodiment |9|, wherein the alcohol is butyl glycol.
[0022] |13| The liquid composition, iii) at least one additive selected from the group consisting of UV stabilizers, surface active substances, low boiling point solvents, pH adjusters, crosslinkers, rheology modifiers, or a combination of at least two of these additives; The liquid composition according to any one of embodiments |1| to |12|, further comprising:
[0023] |14|The liquid composition according to embodiment |13|, wherein the low boiling point solvent is ethanol.
[0024] |15|The liquid composition according to embodiment |13| or |14|, wherein the liquid composition comprises a low-boiling point solvent, preferably ethanol, in an amount of 10 to 90% by weight, more preferably 20 to 85% by weight, and most preferably 30 to 80% by weight, in each case based on the total weight of the liquid composition.
[0025] |16|The liquid composition according to any one of embodiments |13| to |15|, wherein the UV stabilizer is gallic acid, a derivative of gallic acid or a mixture thereof.
[0026] |17|A liquid composition according to embodiment |16|, wherein the derivative of gallic acid is an ester of gallic acid and a sugar.
[0027] |18|A liquid composition according to embodiment |17|, wherein the derivative of gallic acid is gallotannin.
[0028] |19|A liquid composition described in embodiment |18|, wherein the gallotannin is tannic acid.
[0029] |20|The liquid composition according to embodiment |16|, wherein the derivative of gallic acid is an alkyl ester, an alkenyl ester, a cycloalkyl ester, a cycloalkenyl ester or an aryl ester of gallic acid.
[0030] |21|The liquid composition according to embodiment |20|, wherein the ester has 1 to 15 C atoms, preferably 1 to 6 C atoms, in the alkyl, alkenyl, cycloalkyl, cycloalkenyl or aryl group of the ester.
[0031] |22|The liquid composition according to embodiment |21|, wherein the ester is methyl gallate, ethyl gallate, propyl gallate or a mixture of at least two of these esters.
[0032] |23|The liquid composition according to any one of embodiments |13| to |22|, wherein the crosslinking agent is a tetraalkyl orthosilicate.
[0033] |24|The liquid composition according to embodiment |23|, wherein the tetraalkyl orthosilicate is selected from the group consisting of tetramethyl orthosilicate, tetraethyl orthosilicate, tetrapropyl orthosilicate, tetrabutyl orthosilicate, tetrapentyl orthosilicate, orthosilicic acid, at least partially hydrolyzed products of these orthosilicates, and mixtures of at least two of these orthosilicates.
[0034] |25|The liquid composition described in embodiment |24|, wherein the tetraalkyl orthosilicate is tetraethyl orthosilicate (TEOS).
[0035] |26|A liquid composition according to any of embodiments |1| to |25|, wherein the liquid composition comprises i) a complex of a polythiophene and a polyanion, preferably PEDOT / PSS, in an amount of 0.001 to 2.5 wt. %, more preferably 0.005 to 1.0 wt. %, and most preferably 0.01 to 0.5 wt. %, in each case based on the total weight of the liquid composition.
[0036] |27|A liquid composition according to any of embodiments |1| to |26|, wherein the liquid composition comprises water iia) in an amount in the range of 10 to 98% by weight, preferably in the range of 20 to 97% by weight, more preferably in the range of 30 to 96% by weight, and even more preferably in the range of 40 to 95% by weight, in each case based on the total weight of the liquid composition.
[0037] |28|The liquid composition according to any of embodiments |1| to |27|, wherein the liquid composition comprises at least one organic solvent iib) in an amount of less than 10 wt.-%, preferably less than 8.5 wt.-%, and more preferably less than 7 wt.-%, based in each case on the total weight of the liquid composition. In case of two or more organic solvents iib), these amounts define the total amount of organic solvents iib).
[0038] |29| The dry layer prepared from the liquid composition has a density of at least 1 × 10 6 Ω / sq, preferably at least 5×10 6 Ω / sq, and more preferably at least 1×10 7 The liquid composition according to any one of embodiments |1| to |28|, having a sheet resistance of Ω / sq.
[0039] |30|A liquid composition described in any of embodiments |1| to |29|, wherein a dry layer prepared from the liquid composition has an internal transmittance of at least 98%, preferably at least 98.5%, more preferably at least 99%, and most preferably at least 99.5%.
[0040] |31|A liquid composition described in any of embodiments |1| to |30|, wherein a dried layer prepared from the liquid composition has a pencil hardness of at least 6H, preferably at least 7H, more preferably at least 8H, and most preferably at least 9H.
[0041] |32|A liquid composition according to any one of embodiments |1| to |31|, wherein the pH of the liquid composition is 2.5 or higher, more preferably in the range of 2.5 to 6, even more preferably in the range of 2.5 to 5, and most preferably in the range of 2.5 to 4, the pH being determined at a temperature of 25°C.
[0042] |33| A method for producing a layered body, comprising the following process steps: A) providing a substrate; B) applying a liquid composition according to any one of embodiments |1| to |32| onto the substrate; C) at least partially removing the liquid phase ii) from the liquid composition to obtain a layered body including a conductive layer coated on a substrate. A method comprising:
[0043] |34|The method according to embodiment |33|, wherein the application of the liquid composition in process step B) is carried out by slot-die coating, spraying or inkjet printing.
[0044] |35| A layered body obtainable by the method described in embodiment |34|.
[0045] |36| The layered body according to embodiment |35|, wherein the conductive layer of the layered body is characterized by at least one of the following properties (α1) to (α3), preferably by all of these properties: (α1) at least 1×10 6 Ω / sq, preferably at least 5×10 6 Ω / sq, more preferably at least 1×10 7 Sheet resistance in Ω / sq; (α2) an internal transmittance of at least 98%, preferably at least 98.5%, more preferably at least 99%, and most preferably at least 99.5%; (α3) a pencil hardness of at least 6H, preferably at least 7H, more preferably at least 8H, and most preferably at least 9H.
[0046] |37| Use of a liquid composition according to any of embodiments |1| to |32| for the manufacture of an antistatic coating or electromagnetic radiation shield, or for the preparation of a hole transport layer in an organic light-emitting diode (OLED) or organic photovoltaic (OPV) device or organic photodetector (OPD).
[0047] A contribution to achieving the above objectives is made by a liquid composition comprising: i) particles comprising a complex of a polythiophene and a polyanion; ii) Liquid phase. The liquid phase is iia) Water and iib) or less a boiling point in the range of 110 to 250°C, preferably in the range of 120 to 225°C and most preferably in the range of 130 to 200°C, measured at a pressure of 1013 mbar, and - a solubility in water of at least 10% by weight, preferably at least 25% by weight, more preferably at least 50% by weight, and most preferably at least 90% by weight, measured at 25°C; At least one organic solvent having and includes; Including, The liquid phases can be or form an azeotrope.
[0048] According to a preferred embodiment of the liquid composition according to the invention, the liquid composition is a dispersion in which particles i) are dispersed in a liquid phase ii).
[0049] A liquid phase "capable of forming an azeotrope" in the sense of the present invention is a liquid phase which, upon heating, reaches a point at which the composition is an azeotrope. Preferably, it is a liquid phase consisting of water and a high boiling solvent which, upon heating, reaches a point at which the composition is an azeotrope.
[0050] "A solubility in water of at least 10% by weight, measured at 25°C" is indicated if at least 10 g of organic solvent iib) can be dissolved in 100 g of water iia at a temperature of 25°C.
[0051] Surprisingly, it has been discovered that by adding a high boiling organic solvent to the aqueous PEDOT / PSS dispersion in order to slow down the drying rate of the aqueous dispersion, the undesirable increase in sheet resistance can be avoided when using a high boiling organic solvent that can form an azeotrope with water.
[0052] The liquid composition according to the invention comprises as component i) particles comprising a polythiophene and a polyanion. In this context, the general formula [ka] Particularly preferred are polythiophenes having the formula A represents an optionally substituted C1-C5 alkylene radical; R is a linear or branched, optionally substituted C1-C 18 Alkyl radicals, optionally substituted C5-C 12 Cycloalkyl radicals, optionally substituted C6-C 14 Aryl radicals, optionally substituted C7-C 18 represents an aralkyl radical, an optionally substituted C1-C4 hydroxyalkyl radical or a hydroxyl radical, and 0-8 radicals R can be attached to A, and in the case of one or more radicals, can be the same or different.
[0053] The polythiophenes preferably carry in each case an H on the end groups.
[0054] In the context of the present invention, the C1-C5 alkylene radical A is preferably methylene, ethylene, n-propylene, n-butylene or n-pentylene. 18 Alkyl R is preferably linear or branched C1-C 18 Alkyl radicals, such as methyl, ethyl, n- or iso-propyl, n-, iso-, sec- or tert-butyl, n-pentyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, 1-ethylpropyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 2,2-dimethylpropyl, n-hexyl, n-heptyl, n-octyl, 2-ethylhexyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-hexadecyl or n-octadecyl, C5 to C6 12 R represents a cycloalkyl radical. R is, for example, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl or cyclodecyl, C5-C 14 R represents an aryl radical. R is, for example, phenyl or naphthyl, and C7-C 18 R represents an aralkyl radical. R represents, for example, benzyl, o-, m-, p-tolyl, 2,3-, 2,4-, 2,5-, 2,6-, 3,4-, 3,5-xylyl or mesityl. The preceding list serves to illustrate the invention by way of example and should not be considered definitive.
[0055] In the context of the present invention, a large number of organic groups are optionally possible as further substituents of the radical A and / or the radical R, such as alkyl, cycloalkyl, aryl, aralkyl, alkoxy, halogen, ether, thioether, disulfide, sulfoxide, sulfone, sulfonate, amino, aldehyde, keto, carboxylic acid ester, carboxylic acid, carbonate, carboxylate, cyano, alkylsilane and alkoxysilane groups and carboxamide groups.
[0056] Particularly preferred are polythiophenes in which A represents an optionally substituted C2-C3 alkylene radical.Poly(3,4-ethylenedioxythiophene) is very particularly preferred as polythiophene.
[0057] Polythiophenes can be neutral or cationic. In a preferred embodiment, they are cationic, with "cationic" referring only to the charge on the polythiophene backbone. Polythiophenes can carry positive and negative charges in the structural units, depending on the substituents on the radical R, with the positive charges on the polythiophene backbone and the negative charges on the radical R, which is optionally substituted by a sulfonate or carboxylate group. In this connection, the positive charge of the polythiophene backbone can be partially or completely satisfied by anionic groups optionally present on the radical R. Overall, in these cases, the polythiophenes can be cationic, neutral or even anionic. Nevertheless, in the context of the present invention, they are all considered cationic polythiophenes, since the positive charges on the polythiophene backbone are the determining factor. The positive charges are not shown in the formula, since their exact number and position cannot be absolutely determined. However, the number of positive charges is at least 1 and at most n, where n is the total number of all repeating units (identical or different) in the polythiophene.
[0058] To compensate for the positive charge of the polythiophene, the particles i) containing polythiophene further preferably contain a polyanion based on a polymer functionalized with acid groups. Anions of polymeric carboxylic acids, such as polyacrylic acid, polymethacrylic acid or polymaleic acid, or of polymeric sulfonic acids, such as polystyrene sulfonic acid and polyvinyl sulfonic acid, are particularly possible as polyanions. These polycarboxylic and polysulfonic acids can also be copolymers of vinyl carboxylic and vinyl sulfonic acids with other polymerizable monomers, such as acrylic esters and styrene. Further possible polyanions are perfluorinated colloid-forming polyanions, which are commercially available, for example, under the name Nafion®. The molecular weight of the polymers functionalized with acid groups and providing the polyanion is preferably 1000 to 2,000,000, particularly preferably 2000 to 500,000. Polymers functionalized with acid groups or their alkali metal salts are commercially available, for example polystyrenesulfonic acid and polyacrylic acid, or can be prepared by known processes (see, for example, Houben Weyl, Methoden der organischen Chemie, vol. E 20 Makromolekulare Stoffe, part 2, (1987), p. 1141 et seq.). A particularly preferred polyanion is the anion of polystyrenesulfonic acid.
[0059] The particles i) comprise a complex of polythiophene and polyanion, particularly preferably a PEDOT / PSS complex, which is obtained by oxidatively polymerizing a thiophene monomer, preferably 3,4-ethylenedioxythiophene, in the presence of a polyanion, preferably in aqueous solution, preferably by oxidatively polymerizing 3,4-ethylenedioxythiophene in the presence of an anion of polystyrenesulfonic acid.
[0060] The weight average diameter (d 50) is typically in the range of 10 nm to 2000 nm, more preferably in the range of 20 nm to 500 nm, and even more preferably in the range of 25 nm to 50 nm. 50 The value is 50% of the total weight of all particles i), d 50 This indicates that the diameter of the particle can be assigned to the particle with a diameter equal to or smaller than the value (d 50 (The values represent the weight-average particle size.) As in the case of PEDOT / PSS particles dispersed in aqueous solution, the particles usually exist in the form of swollen gel particles, and the particle size above refers to the particle size of the swollen gel particles, determined by ultracentrifugation measurements.
[0061] According to a preferred embodiment of the liquid composition according to the invention, the liquid composition comprises a complex i) of polythiophene and of polyanion, preferably PEDOT / PSS, in an amount of 0.001 to 2.5% by weight, more preferably 0.005 to 1.0% by weight and most preferably 0.01 to 0.5% by weight, in each case based on the total weight of the liquid composition.
[0062] The liquid composition according to the invention comprises as component ii) a liquid phase which comprises water iia) and at least one organic solvent iib) having a boiling point in the range of 110 to 250°C, preferably in the range of 120 to 225°C and most preferably in the range of 130 to 200°C, determined at a pressure of 1013 mbar, and having a water solubility of at least 10% by weight, preferably at least 25% by weight, more preferably at least 50% by weight and most preferably at least 90% by weight, determined at 25°C, wherein the liquid phase is or is capable of forming an azeotrope.
[0063] According to the invention, more preferably, the organic solvent iib) is an alcohol, an ether, preferably diglyme, or a mixture, and therefore more preferably an alcohol selected from the group consisting of ethyl glycol (i.e. 2-ethoxyethanol), butyl glycol (i.e. 2-butoxyethanol), diacetone alcohol (i.e. 4-hydroxy-4-methylpentan-2-one), or a mixture of these alcohols, most preferably with diacetone alcohol.
[0064] According to a preferred embodiment of the liquid composition according to the present invention, the liquid composition further comprises: iii) at least one additive selected from the group consisting of UV stabilizers, surfactants, low boiling point solvents, pH adjusters, crosslinkers, rheology modifiers, or a combination of at least two of these additives.
[0065] The UV stabilizer which may be present as at least one further additive ii) is preferably gallic acid, a derivative of gallic acid or a mixture thereof. Particularly preferred derivatives of gallic acid are esters of gallic acid and sugars, often called tannins or gallotannins (see Roempp Chemie, 10th edition (1999), p. 4391). Further preferred derivatives of gallic acid alkyl, alkenyl, cycloalkyl, cycloalkenyl and aryl esters of gallic acid are preferably those having 1 to 15 C atoms, preferably 1 to 6 C atoms, in the alkyl, alkenyl, cycloalkyl, cycloalkenyl or aryl group of the ester. The most preferred derivatives of gallic acid are gallotannins, such as tannic acid, or alkyl esters of gallic acid, such as methyl gallate, ethyl gallate, propyl gallate, or a mixture of at least two of these esters.
[0066] According to a preferred embodiment of the liquid composition according to the invention, the liquid composition comprises gallic acid, a derivative of gallic acid or a mixture thereof, preferably gallotannin, more preferably tannic acid, in an amount of 0.0001 to 5% by weight, more preferably 0.001 to 2.5% by weight, most preferably 0.01 to 1% by weight, in each case based on the total weight of the liquid composition. If the liquid composition comprises as component iii) a mixture of gallic acid and its derivatives, or a mixture of at least two derivatives of gallic acid, the above amounts refer to the total amounts of these components.
[0067] The crosslinking agent which may be present as at least one further additive iii) is preferably a tetraalkyl orthosilicate. Preferred tetraalkyl orthosilicates are selected from the group consisting of tetramethyl orthosilicate, tetraethyl orthosilicate, tetrapropyl orthosilicate, tetrabutyl orthosilicate, tetrapentyl orthosilicate, at least partially hydrolyzed products of these orthosilicates and mixtures of at least two of these orthosilicates, with particular preference being given to the use of tetraethyl orthosilicate (TEOS).
[0068] According to a preferred embodiment of the liquid composition according to the invention, the liquid composition comprises a tetraalkylorthosilicate, preferably TEOS, in an amount of 0.01 to 15% by weight, more preferably 0.1 to 10% by weight, most preferably 1 to 5% by weight, in each case based on the total weight of the liquid composition. If the liquid composition comprises as component iii) a mixture of two or more tetraalkoxysilanes, the above amounts represent the total amounts of these components.
[0069] In the sense of the present invention, a "low-boiling solvent" which may be present as at least one further additive iii) is a solvent having a boiling point, determined at a pressure of 1013 mbar, below 100° C., preferably below 90° C. and more preferably below 80° C. A preferred low-boiling solvent is ethanol. In this connection, it is also preferred that the liquid composition comprises a low-boiling solvent, preferably ethanol, in an amount of 10 to 90% by weight, more preferably 20 to 85% by weight, most preferably 30 to 80% by weight, in each case based on the total weight of the liquid composition.
[0070] In this connection, it is also preferred that the volume ratio water:ethanol in the liquid composition according to the invention is in the range of 1:1 to 1:25, preferably in the range of 1:2 to 1:20, more preferably in the range of 1:3 to 1:10. The volumes of the individual components are measured before mixing.
[0071] Suitable surface-active substances which can be used as the at least one further additive iii) are, for example, anionic surfactants, such as alkylbenzenesulfonic acids and salts, paraffin sulfonates, alcohol sulfonates, ether sulfonates, sulfosuccinates, phosphate esters, alkyl ether carboxylic acids or carboxylates, cationic surfactants, such as quaternary alkylammonium salts, nonionic surfactants, such as linear alcohol ethoxylates, oxoalcohol ethoxylates, alkylphenol ethoxylates or alkylpolyglucosides, in particular those commercially available under the trademarks Dynol® and Zonyl®.
[0072] The viscosity of the liquid composition according to the present invention is 10 to 100 mPa×s (measured by a rheometer at 20° C. and a shear rate of 100 s -1 Preferably, the viscosity is between 1 and 10 mPa×s, particularly preferably between 2 and 5 mPa×s. Adjustment of the viscosity can be achieved, for example, by adding suitable rheology modifiers as further additives iii).
[0073] According to a preferred embodiment of the liquid composition according to the invention, the pH of the liquid composition is 2.5 or more, more preferably the pH is in the range of 2.5 to 6, even more preferably the pH is in the range of 2.5 to 5, most preferably the pH is in the range of 2.5 to 4, the pH being determined at a temperature of 25° C. The pH can be adjusted by adding a suitable pH regulator, such as an organic or inorganic acid, as further additive iii) to the liquid composition. Suitable acids are inorganic acids, such as sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, silicic acid, or a mixture of at least two of these inorganic acids, or organic acids, such as acetic acid, formic acid, benzoic acid, p-toluenesulfonic acid, PSS, or a mixture of at least two of these organic acids, or a mixture of at least one of these inorganic acids with at least one of these organic acids.
[0074] The liquid composition according to the present invention further comprises iv) at least one further polymer different from the polythiophene and the polyanion It may include, This at least one further polymer iv) preferably acts as a binder. Suitable binders are selected from the group consisting of polyvinyl alcohol, polyvinylpyrrolidone, polyvinyl chloride, polyvinyl acetate, polyvinyl butyrate, polyacrylic esters, polyacrylamides, polymethacrylic esters, polymethacrylamides, polyacrylonitrile, styrene / acrylic esters, vinyl acetate / acrylic esters, ethylene / vinyl acetate copolymers, polybutadiene, polyisoprene, polystyrene, polyethers, polyesters, sulfonated polyesters, polycarbonates, polyurethanes, polyamides, polyimides, polysulfones, melamine-formaldehyde resins, epoxy resins, silicone resins, silane resins, cellulose or a mixture of at least two of these binders. Further useful polymeric binders are preferably also those obtained by adding crosslinking agents such as melamine compounds, capped isocyanates or functional silanes such as 3-glycidoxypropyltrialkoxysilane, tetraethylorthosilicate and tetraethylorthosilicate hydrolysates to crosslinkable polymers such as polyurethanes, polyacrylates or polyolefins, followed by crosslinking. Water-soluble binders such as sulfonated polyesters are particularly preferred.
[0075] According to a preferred embodiment of the liquid composition according to the invention, the liquid composition comprises water iia) in an amount in the range from 10 to 98% by weight, preferably in the range from 20 to 97% by weight, more preferably in the range from 30 to 96% by weight and even more preferably in the range from 40 to 95% by weight, in each case based on the total weight of the liquid composition.
[0076] According to a further preferred embodiment of the liquid composition according to the invention, the liquid composition comprises at least one organic solvent iib), preferably ethyl glycol, butyl glycol, diacetone alcohol or a mixture thereof, more preferably diacetone alcohol, in each case in an amount of less than 10% by weight, preferably less than 8.5% by weight and more preferably less than 7% by weight, based on the total weight of the liquid composition. In the case of two or more organic solvents iib), these amounts define the total amount of organic solvents iib).
[0077] A dry layer prepared with the liquid composition according to the present invention preferably has a surface area of at least 1×10 6 Ω / sq, preferably at least 5×10 6 Ω / sq and more preferably at least 1×10 7 It has a sheet resistance of Ω / sq.
[0078] Dry layers prepared with liquid compositions according to the present invention preferably have an internal transmittance of at least 98%, preferably at least 98.5%, more preferably at least 99%, most preferably at least 99.5%.
[0079] Dry layers prepared with liquid compositions according to the present invention preferably have a pencil hardness of at least 6H, preferably at least 7H, more preferably at least 8H, and most preferably at least 9H.
[0080] The contribution towards achieving the above objectives also includes the following process steps: A) providing a substrate; B) applying a liquid composition according to the present invention onto the substrate; C) at least partially removing the liquid phase ii) from the liquid composition to obtain a layered body including a conductive layer coated on a substrate. This is achieved by a method for producing a layered body, comprising the steps of:
[0081] In process step A), a substrate is first provided, the nature of which depends on the intended purpose for which the composition according to the invention is used. Suitable substrates include films, particularly preferably polymer films, very particularly preferably polymer films of thermoplastic polymers, or glass sheets.
[0082] In process step B), the liquid composition according to the invention is then applied onto a substrate, this application can be carried out by known processes, for example spin-coating, impregnation, pouring, dripping, spraying, misting, knife-coating, slot-die coating, brushing or printing, for example inkjet, screen, gravure, offset or tampon printing, preferably slot-die coating, spraying or inkjet printing, for example with a wet film thickness of 0.5 μm to 250 μm, preferably with a wet film thickness of 2 μm to 50 μm.
[0083] In process step C), at least a portion of the liquid phase ii) is then removed from the liquid composition to obtain a layered body comprising a conductive layer coated on a substrate, which is preferably carried out by drying the composition-coated substrate at a temperature in the range of 20°C to 200°C.
[0084] A contribution to achieving the above-mentioned object is also made by the layered body obtainable by the above-mentioned process. In this context, it is particularly preferred that the conductive layer of the layered body is characterized by at least one of the following properties (α1) to (α3), preferably by all of these properties: (α1) at least 1×10 6 Ω / sq, preferably at least 5×10 6 Ω / sq, more preferably at least 1×10 7 Sheet resistance in Ω / sq; (α2) an internal transmittance of at least 98%, preferably at least 98.5%, more preferably at least 99%, and most preferably at least 99.5%; (α3) a pencil hardness of at least 6H, preferably at least 7H, more preferably at least 8H, and most preferably at least 9H.
[0085] A contribution to achieving the above-mentioned object is also made by the use of a liquid composition according to the invention or a liquid composition obtainable by a method according to the invention for the manufacture of a layered body comprising a substrate and a conductive layer coated on the substrate.
[0086] The layered bodies which can be prepared with the liquid composition according to the invention are eminently suitable for use as electronic components, in particular as conductive or antistatic means, as transparent heating or as electrodes. They can advantageously be transparent.
[0087] These layered bodies can also be used as electronic components, for example in films, packaging of electronic components, finishing of plastic films, and coating of screens.Furthermore, they can be used as transparent electrodes, for example in displays, as replacements for indium-tin oxide electrodes, or as electrical conductors in polymer electronics.Further possible uses are sensors, batteries, solar cells, electrochromic windows (smart windows) and displays, and corrosion protection.
[0088] Considering the low electrical conductivity, high UV stability and high scratch resistance of the coatings obtained with the liquid compositions according to the invention, these liquid compositions are particularly useful for the manufacture of antistatic coatings or electromagnetic radiation shields. They are further particularly useful for the preparation of hole transport layers in organic light emitting diodes (OLEDs) or organic photovoltaic (OPV) devices or organic photodetectors (OPDs).
[0089] The invention will now be described in detail with the aid of non-limiting examples.
[0090] Test Method Determination of sheet resistance The sheet resistance was measured using a High Resistivity Meter Model Hiresta-UX (Model MCP-HT 800) equipped with a ring probe URS RMH214. The measurement was performed at 100V.
[0091] pencil hardness The pencil hardness of the coating is carried out by sliding different pencils of different hardness across the coating deposited on a glass plate according to ISO 15184. The possible effect of pencil marks on the coating is evaluated by eye.
[0092] transparent The internal transmission of the coated substrate is determined with a two-channel spectrometer (Lambda 900, PerkinElmer). Here, to exclude the interference of scattered light, the sample is measured in a photometer sphere (Ulbricht sphere), so that the scattered and transmitted light are detected by a photodetector. The transmission is therefore understood to mean the absorption of the coating and the substrate. The transmission of the pure substrate is first measured. A Melinex 506 film with a thickness of 175 μm is used as the substrate. The coated substrate is then measured. The transmission spectrum is recorded in the visible range, i.e. from 320 nm to 780 nm with a step width of 5 nm.
[0093] The standard color value Y of a sample is calculated from the spectrum according to DIN 5033, based on a 10° observer angle and light type D65. The internal transmittance is calculated from the ratio of the standard color values of the substrate with coating (Y) and the substrate without coating (Y0). The internal transmittance corresponds to Y / Y0 x 100 (%). For simplicity, only the transmittance is referred to in the following. EXAMPLES
[0094] Example 1 Clevios P VP CH 8000 (Heraeus) (PEDOT / PSS weight ratio 1:20; solids: 2.8 wt%) was mixed with different amounts of different solvents (all fully soluble in water) as shown in Table 1. For example, to obtain sample 2, 95 g of Clevios P VP CH 8000 was mixed with 5 g of butyl glycol and stirred for 10 minutes. The dispersion was tested for nozzle clogging. The samples were spin-coated on glass substrates and dried at 200° C. for 15 minutes. The sheet resistance was measured. Table 1 summarizes the results. Samples 2, 3, 4, 5 and 6 of the invention are compared with reference samples 7 and 8.
[0095] [Table 1]
[0096] Only high boiling solvents that form azeotropes with water do not significantly change the resistivity of the CH 8000 film, whereas DMSO or ethylene glycol do.
[0097] Example 2 0.1 g of tannic acid is dissolved in 84 g of ethanol. 12.6 g of Clevios P (Heraeus) is placed in a 250 ml glass beaker. The ethanol solution of tannic acid is added to the Clevios P dispersion under stirring. 3.1 g of tetraethyl orthosilicate is added to the mixture. The pH is adjusted to 3.3. Various amounts of additional solvent (as shown in Table 2) were added to the dispersion. The mixture is stirred for 30 minutes at room temperature.
[0098] Films with a wet thickness of 12 μm are deposited on alkali-free glass using a wire bar and subsequently dried for 20 min at 120° C. The results are shown in Table 2. Inventive samples 10 and 11 are compared with reference samples 9 and 12-16.
[0099] [Table 2]
[0100] Example 3 Clevios P VP CH 8000 was concentrated to 3.24% solids. Different high boiling point solvents were added in different amounts to this "Clevios CH8000 concentrate" (PEDOT / PSS-weight ratio 1:20; solids: 3.24% by weight). Samples were spin-coated on glass substrates and dried at 200°C for 15 min. Sheet resistance was determined as shown in Table 3. The layer thickness of the samples was 200 nm.
[0101] [Table 3]
[0102] Inventive samples 18-24 are compared with reference sample 17.
Claims
1. 1. A liquid composition comprising: i) particles comprising a complex of a polythiophene and a polyanion; ii) a liquid phase, said liquid phase being iia) water; iib) Below - boiling point in the range of 110 to 250°C measured at a pressure of 1013 mbar and - a solubility in water of at least 10% by weight, measured at 25°C; At least one organic solvent having and Including, The liquid phase is or can form an azeotrope; liquid composition.
2. 2. The liquid composition of claim 1, wherein the polythiophene is poly(3,4-ethylenedioxythiophene) and the polyanion is the anion of polystyrene sulfonic acid.
3. The liquid composition according to claim 1 or 2, wherein the organic solvent iib) is an alcohol, an ether or a mixture thereof.
4. 4. The liquid composition of claim 3, wherein the alcohol is selected from the group consisting of ethyl glycol, butyl glycol, diacetone alcohol, diethylene glycol dimethyl ether, or mixtures thereof.
5. The liquid composition of claim 4, wherein the alcohol is diacetone alcohol.
6. The liquid composition according to any one of claims 1 to 5, wherein the liquid composition further comprises as at least one further additive iii) a low boiling point solvent, wherein the low boiling point solvent is ethanol.
7. The liquid composition according to any of claims 1 to 6, wherein said liquid composition further comprises as at least one further additive iii) a cross-linking agent, said cross-linking agent being tetraethyl orthosilicate (TEOS).
8. The liquid composition according to any one of claims 1 to 7, wherein the liquid composition comprises the complex of polythiophene and polyanion i) in an amount ranging from 0.001 to 2.5 wt. %, based on the total weight of the liquid composition.
9. The liquid composition according to any one of claims 1 to 8, wherein the liquid composition comprises water iia) in an amount ranging from 10 to 98% by weight, based on the total weight of the liquid composition.
10. 10. The liquid composition according to any one of claims 1 to 9, wherein the liquid composition comprises the at least one organic solvent iib) in an amount of less than 10% by weight, based on the total weight of the liquid composition.
11. The dry layer prepared from the liquid composition has a thickness of at least 1×10 6 The liquid composition according to any one of claims 1 to 10, having a sheet resistance of Ω / sq.
12. A method for producing a layered body comprising the following process steps: A) providing a substrate; B) applying a liquid composition according to any one of claims 1 to 11 onto said substrate; C) at least partially removing the liquid phase ii) from the liquid composition to obtain a layered body comprising a conductive layer coated on the substrate. A method comprising:
13. 13. The method according to claim 12, wherein the application of the liquid composition in process step B) is carried out by slot-die coating, spraying or inkjet printing.
14. A layered body, obtainable by the method according to claim 12 or 13.
15. Use of a liquid composition according to any one of claims 1 to 11 for the formation of an antistatic coating or an electromagnetic radiation shield, or for the preparation of a hole transport layer in an organic light emitting diode (OLED) or an organic photovoltaic (OPV) device or an organic photodetector (OPD).
Citation Information
Patent Citations
Conductive organic-inorganic hybrid materials
JP2001506797A
Solution for hole injection layer, organic el element manufacturing method, and organic el element
JP2008294349A
Method for manufacturing organic light emitting display
JP2012054244A
Conductive polymer compositions and films
JP2015534213A
Liquid composition comprising particles of a conductive polymer and an organic solvent that forms an azeotropic mixture with water
JP7256213B2